Optical Network Management by ONOS-Based SDN Controller - Romanov, O.I.; Svyd, I.V.; Korniienko, N.I.; Romanov, A.O. (Radiotekhnika, 2022)
The possibilities to manage the optical network with a logically centralized SDN control plane based on the Open Network Operating System (ONOS) are investigated. The structure of the controller and its main functional blocks are considered ensuring the collection of information about the state of network elements, the solution of the main control tasks, interaction of control systems built on different technological bases, are considered. The role and place of the open network operating system in the controller structure are shown, the description of the ONOS multilevel architecture in the form of a set of functional modules is given, the purpose and functions of the ONOS subsystems are analyzed, protocols and interfaces making it possible to present the SDN network as a model are described. The peculiarity of the model is that the managed network can be represented as a set of virtual network functions. Therefore, the control process becomes independent of which vendor's equipment was used to build the network, as well as whether the network is built on real physical elements or virtual ones. Using the ONOS allows you to build a logical centralized control plane in the SDN networks. The existing set of functional modules, services and interfaces in the ONOS allows you to perform optical network management tasks. For the further development of the ONOS, it is necessary to develop mathematical models and methods for the optimal solution of control problems in various operating conditions, which will become application-level software modules in the future.